Phrenic nerve conduction studies as a biomarker of respiratory insufficiency in amyotrophic lateral sclerosis. Issue 3 (18th May 2016) - Jenkins, J. A. Liberty; Sakamuri, Sarada; Katz, Jonathan S.; Forshew, Dallas A.; Guion, Lee; Moore, Dan; Miller, Robert G.
Abstract: Our objective was to examine the value of phrenic nerve conduction studies (PNCS) in quantifying diaphragm dysfunction in ALS, as no ideal test of respiratory insufficiency exists in ALS. We prospectively recorded bilateral PNCS, forced vital capacity (FVC), maximum inspiratory pressure (MIP), sniff nasal inspiratory pressure (SNIP), respiratory rate, ALSFRS-R, and respiratory symptoms in 100 ALS patients attending our clinic over a nine-month period. Survival data were collected for two years. Results showed that PNCS were reproducible and well tolerated. When the Pamp was abnormal (<0.3 mV), the relative risk of a respiratory rate >18 was 7.2 (95% CI 2.2–37.2, p <0.01) compared with a Pamp ≥0.3 mV. Similarly, the relative risk of orthopnea was 3.5 (95% CI 1.6–8.7, p <0.01) and dyspnea 2.4 (95% CI 1.4–4.0, p <0.01). FVC had the strongest correlation with Pamp (R 2 = 0.48 ( p <0.001)). Fourteen of 15 patients with a FVC <50% had a Pamp <0.3 mV. However, eight with a Pamp <0.3 had a FVC >80%. The median survival was 1.07 years when the Pamp was <0.3 mV and >2 years when the Pamp was >0.3 mV ( p <0.001). In conclusion, the phrenic Pamp correlated closely with multiple symptoms, signs, and laboratory measures of respiratory insufficiency and may prove to be a useful biomarker of respiratory dysfunction in ALS.